2011
DOI: 10.1208/s12248-011-9299-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin—A Potential Marker of Drug Exposure in Atazanavir-Based Antiretroviral Therapy

Abstract: Abstract. The objective of this work was to examine the atazanavir-bilirubin relationship using a populationbased approach and to assess the possible application of bilirubin as a readily available marker of atazanavir exposure. A model of atazanavir exposure and its concentration-dependent effect on bilirubin levels was developed based on 200 atazanavir and 361 bilirubin samples from 82 patients receiving atazanavir in the NORTHIV trial. The pharmacokinetics was adequately described by a one-compartment model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…However, despite having nomograms for the calculation of exposition to ATZ based on the turnover concept and indirect response model, which support the conventional model in this area,20 the data obtained by applying our present model were not consistent with those obtained by applying nonograms published by other authors 9,1820…”
Section: Introductioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, despite having nomograms for the calculation of exposition to ATZ based on the turnover concept and indirect response model, which support the conventional model in this area,20 the data obtained by applying our present model were not consistent with those obtained by applying nonograms published by other authors 9,1820…”
Section: Introductioncontrasting
confidence: 84%
“…With respect to the model for the quantification of ATZ-bilirubin interaction, previous studies have shown a positive correlation between ATZ exposure and hyperbilirubinemia that allow us to use BIL as a marker of ATZ exposure 1820…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our population, we did not observe any association with the explored parameters; however, the relevant proportion of missing data could have influenced such finding masking the real effects in terms of increased/reduced hazard of adverse events occurrence. Moreover, only baseline markers were analyzed, while the effect of current markers may be crucial, for instance the raise levels of bilirubin during atazanavir-containing antiretroviral therapy [28]. We decided not to perform a time-dependent analysis given the high rate of missing information in the baseline variables.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the stringent algorithm that we used to classify self-reported adherence in the questionnaire and the difference between perceived adherence and objective adherence. Bilirubin level, which is more objective, has been linked to adherence to atazanavir (25,26). Of note, our data set served for external validation of the use of bilirubin level to detect suboptimal atazanavir exposure, as reported elsewhere (27).…”
Section: Discussionmentioning
confidence: 85%